Experimental Measurement And CFD Simulation on the Hydrodynamics of An Internal-Loop Airlift Reactor - Shi, Yan Liew; Zhi, Yee Lam; Jolius, Gimbun (EDP Sciences, 2017)
This paper concerns with the experimental measurement and computational fluid dynamics simulation on local hydrodynamics of a gas-liquid internal-loop airlift reactor. The aim of this work is to study the sensitivity of the drag models and the significance of considering the lift force on the predictive accuracy of the simulation. The experimental analysis was carried out using laser Doppler anemometry at three different heights (i.e. Y = 0.20 m, 0.30 m and 0.38 m) across the riser and downcomerat volumetric flow rate of 0.30 m3/h to provide validation for the simulation results. A transient three-dimensional gasliquid internal-loop airlift reactor was carried out using FLUENT 16.2 by implementing the two-fluid model approach. The Eulerian-Eulerian multiphase and standard κ-ε dispersed turbulence model wereemployed in this study. Results suggest that the spherical drag model performed poorly and that the drag model governed by Rayleigh-Taylor shows promising accuracy in the prediction of overall mean axial liquid velocity. On the other hand, the consideration of lift model shows slightly improvement in accuracy. These findings may serve as a guidance for future scale-up and design of airlift reactor studies.